Novas tecnologias e livro didáticos da EJA: uma abordagem pedagógica por meio do gênero propaganda - PEDROSO, Luis Marcelo de Araújo (Universidade Federal do Pará, 2019)
This work sought to propose a pedagogical approach, using the advertising genre, considering the use of NICTs and a relationship with the EJA Didactic Book (3rd stage), of a public school in the outskirts of Belém. relationship occurred in the learning of the reading and writing competence in the teaching-learning process of the students. Thus, it was important to describe the EJA, the textbook, NTICs, proposal for action and observation in the proposed activities. For the study of the mother tongue, use the language of gender, analyze its structure, verbal / nonverbal language and as predominant language functions. It was argued that the appropriation of technological shoes would broaden the knowledges and orientation of students of the moment for the practical purpose. A literature used as authors such as, Souza (1998), Bakhtin (2003), Menegassi (2005) and Koch (2015). The work also revealed that, although it was used, NICTs in conjunction with LDs for Portuguese language teaching still exist in the challenges for the most effective development of this type of referral. This is justified because there are teachers who are not well prepared and interested in working with the new technologies. In addition, many schools do not offer a suitable structure for this type of work in the function of low investment in the area. On the other hand, students are very receptive to NICTs. They escape, learn and adhere to their learning, especially in the activities that enhance the relationship with their possibilities of articulation with the labor market (formal and informal) and subsistence.